Assessment of Gestational Diabetes Mellitus Outcomes for Hispanic Women Living in the Rio Grande Valley. (September 2019) - Somohano-Mendiola, Norma; Champion, Jane Dimmitt; Vatcheva, Kristina
Introduction: Gestational diabetes mellitus (GDM) among women living along the U.S.–Mexico border are approximately twice that of the general population of pregnant U.S. women. This study compared outcomes for Hispanic pregnant women diagnosed and treated for GDM (i.e., two abnormal 3-hour oral glucose tolerance tests [OGTT]) with those who were screened but had only one abnormal 3-hour OGTT and therefore received no treatment. Methods: Retrospective chart review of pregnant Hispanic women of Mexican origin ( N = 95), with GDM ( N = 41) or one abnormal 3-hour OGTT value ( N = 54) who delivered between January 1, 2015, and December 31, 2017. Results: No significant differences were found between the two groups with regard to sociodemographic variables, hyperbilirubinemia, or other adverse neonatal outcomes. Comparisons identified differences between women with and without adverse neonatal outcomes concerned type of delivery; there were more C-sections among women with GDM. Conclusion: Pregnant women with one abnormal 3-hour OGTT value are at risk of giving birth to neonates with biomarkers similar to those diagnosed and treated for GDM. The treatment of hyperglycemia in Hispanic women of Mexican origin with one abnormal 3-hour OGTT value may improve the health outcomes and quality of life of the mother and the neonate. More research is warranted to clarify the risk of adverse outcomes of diverse pregnant women who do not meet guidelines for diagnosis of GDM.